Questions in Smart Digital Environments - Freestone, Melvin; Mason, Jon (Frontiers in Education, 2019)
Innovations in digital technologies have catalysed significant transformations of teaching and learning. Searching static webpages has evolved into dynamic online social networking and user generated content, and more recently interaction with intelligent services. The distinguishing features are embodied in the keywords – search, social, and smart. While search engines maintain a pivotal role in the web, social media now rivals them for dominance. The current era of smart technologies, based around big data and artificial intelligence, further extends the frontier of possibilities. With transition to the ‘world of smart’ in mind, we explore ways in which the natural human ability of questioning might be scaffolded and developed. Digital environments provide diverse opportunities to construct learning in ways that bring life inside and outside school closer together. They open-up new horizons for learners to engage in a curious dialogue with experience. Yet the answer driven paradigm of ‘search’ abbreviates much of the scope for questioning embedded in the expression and growth of curiosity. In this paper, we describe a set of generic generative questions that has the potential to transform questioning in digital environments. In so doing a conceptual analysis of how learners’ questioning might be scaffolded is presented. Applicable to all areas of learning, these questions promote imaginative thinking and deep understanding on which knowledge building and creation is predicated. Question driven dialogues generate critical and creative thinking, and thereby help to enact current mandates for creativity and knowledge building. The conformity emanating from the Global Education Reform Movement is anomalous with prescriptive curriculum texts and standardized tests emphasising answers, not questions. Clever use of digital environments has the potential to catalyse a shift towards a questions-based approach to teaching and learning.